Asymmetric Information and Quantization in Financial Economics - Raymond J. Hawkins; B. Roy Frieden (International Journal of Mathematics and Mathematical Sciences)
We show how a quantum formulation of financial economics can be derived from asymmetries with respect to Fisher information. Our approach leverages statistical derivations of quantum mechanics which provide a natural basis for interpreting quantum formulations of social sciences generally and of economics in particular. We illustrate the utility of this approach by deriving arbitrage-free derivative-security dynamics.